A critical review of traditional Chinese medicine use amongst women with menopausal symptoms. (December 2014) - Peng, W.; Sibbritt, D. W.; Hickman, L.; Kong, X.; Yang, L.; Adams, J.
Abstract Objectives To provide the first critical review of traditional Chinese medicine (TCM) use amongst symptomatic menopausal women, drawing upon work examining the perspectives of both TCM users and TCM practitioners. Methods A search was conducted in three English-language databases (MEDLINE, CINAHL and AMED) and three Chinese-language databases (CNKI, VIP and CBM Disc) for 2002–2013 international peer-reviewed articles reporting empirical findings of TCM use in menopause. Results A total of 25 journal articles reporting 22 studies were identified as meeting the review inclusion criteria. Chinese herbal medicine appears to be the most common therapy amongst symptomatic menopausal women, and vasomotor symptoms and emotional changes are the most frequent symptoms for which TCM is sought. However, evidence regarding the prevalence of TCM use and users' profile in menopause is limited. Existing studies are of varied methodological quality, often reporting low response rate, extensive recall bias and a lack of syndrome differentiation. Conclusions This review provides insights for practitioners and health policy-makers regarding TCM care to symptomatic menopausal women. More nationally representative studies are required to rigorously examine TCM use for the management of menopausal symptoms. Syndrome differentiation of menopausal women is an area which also warrants further attention.